Personalizing therapies over the course of hormone receptor‐positive/HER2‐negative metastatic breast cancer - Akshara Singareeka Raghavendra; Senthil Damodaran; Carlos H. Barcenas; Suzanne A. Fuqua; Rachel M. Layman; Debu Tripathy (CA: A Cancer Journal for Clinicians, 2026)
ABSTRACT The hormone receptor (HR)‐positive/human epidermal growth factor receptor 2 (HER2)‐negative breast cancer subtype accounts for most early and metastatic breast cancer (MBC) cases. HR‐positive/HER2‐negative MBC is characterized by a relatively prolonged, although variable, disease course and substantial intertumoral and intratumoral heterogeneity. Although endocrine‐based therapies remain the cornerstone of treatment, nearly all patients eventually develop resistance, which is increasingly addressed with biologically targeted agents and newer‐generation cytotoxic drugs. This review summarizes the current understanding of HR‐positive/HER2‐negative MBC biology, highlighting mechanisms of intrinsic and acquired resistance, including driver genomic alterations that, along with clinical factors, help guide therapeutic choices and sequencing. The authors specify and discuss how genomic and transcriptomic profiling inform treatment selection and how side effects and overall patient experience are considered in decision making. Advances in targeted therapies, such as CDK4/6 (cyclin‐dependent kinase 4/6), PI3K (phosphatidylinositol 3‐kinase), and AKT (protein kinase B) inhibitors, and next‐generation estrogen receptor degraders are reviewed along with the expanding role of antibody–drug conjugates and biomarker‐guided tumor‐agnostic biologic therapies. The authors also explore evolving biologic concepts, including the impact of the tumor microenvironment on resistance and disease progression, and consider the distinct clinical behavior of invasive lobular carcinoma and current approaches. Emerging data from contemporary clinical trials promise to refine clinical and biomarker‐driven algorithms and improve outcomes for patients with HR‐positive/HER2‐negative MBC. Ongoing multi‐omic research and adaptive clinical strategies will be essential to further the application of precision oncology in this most common subtype of MBC. Importantly, patient‐reported outcomes, shared decision making, and real‐world evidence are increasingly useful in formulating comprehensive care plans, guidelines, and policy. The modern treatment landscape features a personalized approach that integrates clinical features, biomarkers, and patient preferences across the disease continuum.